Digital community development platforms: engineering, land and architectural solutions for the village of the future (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The article explores an integrated digital platform approach to the development ofrural territories in Ukraine, focusing on comprehensive management of engineering, land, andarchitectural resources at the community level. The relevance of the study is determined by the needto overcome fragmented decision-making, outdated spatial data, and limited institutional capacity oflocal communities, especially in the context of post-war recovery and sustainable ruraldevelopment.The paper proposes a conceptual model of an integrated digital platform that combinesengineering assessment and modelling (White Due Diligence Engineering), land and legal analysis(Triada Land & Legal), and urban and architectural planning tools (SigmaGeoPort Urban). Thefunctional capabilities of the platform are analyzed, including risk identification, spatial scenariomodelling, infrastructure planning, land-use optimisation, and preparation of investment-readyproject packages.The study demonstrates the practical impact of digital platforms on improving transparency ofasset management, reducing technical and legal risks, accelerating investment project preparation,and supporting evidence-based spatial planning. Particular attention is paid to the role of suchplatforms in empowering young professionals by providing access to real data, applied analyticaltools, and interdisciplinary skills at the intersection of GIS, engineering, architecture, and territorialdevelopment. The findings confirm that integrated digital platforms represent a key instrument forsustainable rural development and the formation of resilient, investment-attractive communities inUkraine.
Keywords: digital platforms; rural development; Smart Village; spatial planning; engineering infrastructure; land management; community development; GIS; post-war reconstruction